Performance analysis of nature inspired heuristics for survivable virtual topology mapping - (:unkn) unknown (My University, 2009)
The high capacity of fibers used in optical networks, can be divided into many channels, using the WDM technology. Any damage to a fiber causes all the channels routed through this link to be broken, which may result in a serious amount of data loss. As a solution to this problem, the virtual layer can be mapped onto the physical topology, such that, a failure on any physical link does not disconnect the virtual topology. This is known as the survivable virtual topology mapping problem. In this study, we investigated the performance of two popular nature inspired heuristics, namely, evolutionary algorithms and ant colony optimization, in finding a survivable mapping of a given virtual topology while minimizing the resource usage. Our results show that both nature inspired heuristics perform remarkably well for this problem. Furthermore, both methods can obtain high quality solutions in less than a minute.